(untitled) (Bioscience Journal, 2020)
The aim of research was to evaluate the meat quality of Nellore young bulls in grazing supplemented with or without addition of lipids. Twenty–four young bulls, 301 ± 5.8 kg in body weight, were used in the experiment and randomly distributed into four groups according to treatment: only Panicum maximum cv. Mombasa grass; Mombasa grass with concentrated supplementation based on soybean meal; Mombasa grass with concentrate containing lipids from soybean oil; and Mombasa grass with concentrate containing lipids derived from soybean grains. There were no differences (P>0.05) between the treatments for temperature, pH, thawing, cooking and total losses, shear force, sarcomere length and collagen in bulls. Nellore young bulls raised in fertilized and irrigated Mombasa grass fed Mombasa grass only or supplemented with or without addition of lipids were similar regarding meat quality.